PMP Exam Prep : accelerated learning to pass the project management professional (PMP) exam - Mulcahy, Rita (Minnesota: RMC Publishing, 2020)
"Offering hundreds of sample questions, thought-provoking exercises, and critical time-saving tips, this book will help you pass the PMP exam on your first try."--Page 4 of cover.
"Aligned with the PMBOK® Guide, sixth edition and the 2021 Examination Content Outline (ECO). For exams taken after January 2, 2021."
Includes bibliographical references (pages 507-521) and index.
Keywords: Project management -- Examinations, questions, etc; Project management -- Examinations -- Study guides; Project management; Project management -- Examinations; Examinations; Study guides; Study guides